The Role Of Brand Trust In Mediating The Influence Of Green Product, Corporate Social Responsibility, And E-Wom On Purchase Decisions: A Study On Avoskin Skincare - Nushair, Muhammad Rois; Astini, Rina (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study explores the role of brand trust in mediating the influence of green products, corporate social responsibility (CSR), and e-WOM on purchase decisions. With the backdrop of the rapid growth of the skincare industry in Indonesia, the research aims to understand the factors influencing consumer decisions. The methodology employed is a survey with a quantitative approach, analyzed using Structural Equation Modeling (SEM). The results indicate that green products, CSR, and e-WOM have a positive and significant impact on purchase decisions, with brand trust serving as a mediating variable that enhances this influence. These findings provide valuable insights for marketers in developing sustainable and responsive strategies to market trends.